Setting up the Nyoongar Tent Embassy: A report on Perth media - Kerr, Thor; Cox, S. (Ctrl-Z Press, 2013)
On 12 February 2012, people concerned with native-title negotiations between the government of Western Australia and the Nyoongar people gathered at Matagarup on Heirisson Island and, inspired by the 40th anniversary of the Aboriginal Tent Embassy in Canberra, established the Nyoongar Tent Embassy. News reports on the Nyoongar Embassy initially focussed on demands for justice and recognition of native title, but this focus soon shifted to the alleged illegality of camping at Heirisson Island, the threat of public nuisance and the force used by police in raids against the Embassy. This report is intended to further understandings of popular media representations of the Nyoongar Tent Embassy at Heirisson Island and the actions taken by authorities to eradicate it. The report is based on an archive of 104 media texts produced by the electronic and print media in February and March 2012, which we put to close critical examination. We conclude that media reports, with few notable exceptions, positioned the Tent Embassy as a lawbreaking, menacing ‘Aboriginal protest camp’. This positioning - together with selective reporting practices - legitimised the repeated police raids against citizens gathering at what was in fact a state-listed Aboriginal heritage site for discussions on native title.Tent Embassy participants were arrested, subjected to violent police raids that had them fearing for the safety of their children and themselves, and had their possessions regularly seized for allegedly ‘camping illegally on a public reserve’. While police spokespeople, senior bureaucrats, politicians and journalists cited illegal camping as the justification for aggressive police action, in fact arrests were made not for ‘illegal camping’ but for obstructing police in the action of forcibly preventing Embassy participants from exercising rights to customary use as recognised under the Aboriginal Heritage Act 1972 (WA). The apparent failure of the government to protect the rights of Nyoongar citizens at the Tent Embassy and the ways in which Perth news media failed to identify this neglect as a crucial component of the story are the critical issues at the centre of this report.